Os entrelaçamentos das vidas/corpos nos cotidianos escolares : a formação continuada de professores/as com a diferença - Amorim, Fábio Luiz Alves de (2017)
To problematize the processes of continuous formation of teachers with the difference, from the curricula woven with the lives / bodies that inhabit and pulsate, in their multiplicity, in the everyday school. It resorts to the perspective of Foucauldian problematization that helps to think life as a work of art, provoking possible movements and displacements, designing ways to re-create new / other forms of life. It proposes to think, reflect and "future" the dominant hegemonic discourse to break with the idea of a unique curriculum and unique formation. It has as methodological presuppositions the research in the / of / with the daily ones, moved from the networks of conversations assumed like power of the collective action in the school and like possibility of thinking next to the practitioners the movements of continuous formation and, in this direction, the pulsations curricular with which teachers and students weave the knowledge and do. The networks of conversations took place in the daily life of a state public school in the outskirts of Serra / ES, at times of planning, execution of projects and formations planned in the school calendar, involving 24 teachers, 02 pedagogues and 46 students, and the data produced in the years 2016 and 2017. The study helps to understand: the life experiences of teachers and students in everyday school; the difference as complex and transitional negotiation, procedurally manifest in the flows of representations and significations in the spaces of enunciation, in the "inter-places" and in the always contingent, open and indefinite frontiers; and the plots lived by the subjects immersed in events, in the discursive production of the other and of himself, leading to the emergence of powerful threads for the production of new / other problematization in search of the right to be and to be in the world. The bet of the thesis in the conversational dimension as inseparable from the processes of knowledge production, indicated that the interweaving of the lives / bodies in the daily ones of school they potentiate the continuous formation of teachers / perspective of the difference.